(untitled) (Economic and Political Thought, 2013)
The current financial crisis showed that the European Union economic construction lacks resistance to external shocks and that the macro-economic and financial policy of some Euro Zone states is very incautious. The necessary reconstruction consists in the creation of fiscal and banking union supported by common financial instruments. Further, deeper reforms are expected.